The effect of grip position on golf driving accuracy and distance - D´Arcy, M.; Heisler, S.; Quilling, E.; Strüder, H. K.; Chevalier, A. (Journal of Sports Sciences, 2021)
The grip position (GP) in golf substantially affects performance outcomes such as shot accuracy and hitting distance. However, it is unknown which specific GP (i.e., strong, neutral, weak) produces the desired shot outcomes. The current study investigated the impact of five systematically manipulated GPs using 15° increments between -30° (strong) and +30° (weak) on driving accuracy and distance. Data were collected using a Trackman™ doppler radar-based system for 28 amateur recreational golfers with a driver clubhead-speed range between 120 km/h and 153 km/h (M = 138.93 km/h, SD = 14.41) and a handicap range between -3 and -36 (M = -15.0, SD = 8.0). The results showed that GP significantly affected six dependent variables on accuracy (sideways deviation (left and right), accuracy absolute, clubface angle, club path angle, face to path angle, launch direction) and two outcomes on distance (clubhead speed and driving distance total). Overall, the optimal performance on driving accuracy and distance was found for the neutral and stronger GPs. Weaker GPs revealed significantly more adverse accuracy and distance effects. These results suggest asymmetric outcome effects of symmetrical GP manipulation. They also have practical implications for coaches and golfers intending to improve driving accuracy while maximizing driving distance.